Optimalisasi Limbah Ternak Melalui Pelatihan Pembuatan Pupuk Organik Padat dan Cair sebagai Upaya Penanggulangan Pencemaran - Ridwan, Awaludin; Rastono, Adi; Fanani, Ahmad; Indarwati, Lisa Dwifani; Wulandari, Kartika (Yayasan Habiburrahman Jamalu Bina Ummat, 2026)
This community service program aims to enhance the awareness and skills of the Mulyoagung Village community in sustainably managing livestock waste through the production of solid and liquid organic fertilizers. The activities were conducted using socialization, training, hands-on practice, and evaluation methods through pre-tests and post-tests involving 50 livestock-owning participants. The results indicate a significant improvement in participants’ knowledge and skills in understanding the environmental impacts of livestock waste and the techniques for processing it into organic fertilizer. Participants were able to independently practice the fertilizer production process and demonstrated readiness to apply the training outcomes. This program contributes to reducing environmental pollution and supports sustainable agriculture based on local potential.